Is There a Relationship between Patellofemoral Alignment and Osgood–Schlatter Disease? A Case-Control Study - Seyfettinoğlu, Fırat; Köse, Özkan; Oğur, Hasan Ulaş; Tuhanioğlu, Ümit; Çiçek, Hakan; Acar, Baver (The Journal of Knee Surgery, 2020)
This study was aimed to investigate the role of anatomic variations in patellofemoral alignment in patients with or without Osgood-Schlatter disease (OSD) and to determine the potential anatomic risk factors that may play role in the etiology. This prospective observational case-control study was conducted on two groups of adolescent patients. Group 1 comprised patients who were diagnosed as having OSD and group 2 consisted of an equal number of age-matched patients who presented to the outpatient clinic with traumatic knee injury and underwent knee radiographic examination but without a diagnosis of OSD. Age, height, weight, body mass index (BMI), dominant side, and level of sporting activity were recorded. Quadriceps (Q) angles were measured using a long-arm goniometer with patients lying in the supine position with their knees in full extension and contracting the Q muscles. On anteroposterior, lateral knee, and tangential patella (Merchant and Laurin views) radiographs, the following measurements were performed: Insall–Salvati (IS), Caton–Deschamps (CD), and Blackburne–Peel (BP) indexes, congruence angles, lateral patellofemoral angles, sulcus angles, and patella type according to Grelsamer's morphology classification. Both groups were similar in respect of age (p = 0.160), sex (p = 0.311), height (p = 0.326), weight (p = 0.596), BMI (p = 0.153), and dominancy (p = 0.500). The rate of patients engaged in sports activities was significantly greater in the OSD group (p = 0.003). No significant difference was determined between the groups in respect to IS index, CD index, BP index, sulcus angle, lateral patellofemoral angle, and congruence angle (p–values: 0.358, 0.995, 0.912, 0.802, 1.000, and 0.907, respectively). The mean Q angle was measured as 15.6 ± 2.2 degrees in the OSD group and 14.3 ± 2.5 degrees in the control group (p = 0.014). Despite the difference being statistically significant, it was clinically insignificant because the difference was only 1.3 degrees. The principle etiologic factor seems to be increased physical activity rather than subtle variations is patellofemoral anatomy and alignment of extensor mechanism.
Keywords: Osgood-Schlatter; patellofemoral alignment; etiology; patella alta; patella baja